IMPLICIT PARTICIPANTS IN MENTAL PROCESS: A FUNCTIONAL GRAMMAR ANALYSIS - Gartika Rahmasari; Iis Kurnia Nurhayati (JALL (Journal of Applied Linguistics and Literacy), 2019)
Mental processes are process of sensing and are realized by verbs of cognition, affection, perception, and volition. Those types of verbs are transitive verbs, which mean they need object. This means that there is someone who senses (Senser) and there is something that is sensed (Phenomenon). There are three types of phenomenon, Phenomenon of Thing, Phenomenon of Act and Phenomenon of Fact. These two participants—Senser and Phenomenon—always exist in the processes, whether explicitly or implicitly. However, some clauses that are mental processes do not include one of the participants, eitherSenser or Phenomenon. There is even some data that do not include both participants. Thus, the aim of this paper is to probe implicit participants that might exist in mental processes, using content analysis as a method. The result, Implicit Participants, namely Implicit Senser and Implicit Phenomenon, can be retrieved from sentence that comes before the mental processes. The mental processes were then paraphrased and deconstructed to form a complete mental processes that include both participants, Senser and Phenomenon.Keywords: Mental process, Senser, Phenomenon, implicit